Identities involving skew Lie product and a pair of generalized derivations in prime rings with involution - Bhushan, Bharat; Sandhu, Gurninder Singh; Kumar, Deepak (Armenian Journal of Mathematics, 2021)
In this paper, we consider skew Lie product on an involutive ring and study several algebraic identities for it, which include generalized derivations of the ring. The results give information about the commutativity of the ring and a description of the generalized derivations.